An Emerging Role for SNARE Proteins in Dendritic Cell Function - Collins, Laura E.; DeCourcey, Joseph; Soledad di Luca, Mariana; Rochfort, Keith D.; Loscher, Christine E. (Frontiers in Immunology, 2015)
Dendritic cells (DCs) provide an essential link between innate and adaptive immunity. At the site of infection, antigens recognised by DCs via pattern-recognition receptors such as Toll like receptors (TLR), initiate a specific immune response. Depending on the nature of the antigen, DCs secrete distinct cytokines with which they orchestrate homeostasis and pathogen clearance. Dysregulation of this process can lead to unnecessary inflammation which can result in a plethora of inflammatory diseases. Therefore, the secretion of cytokines from DCs is tightly regulated and this regulation is facilitated by highly conserved trafficking protein families. These proteins control the transport of vesicles from the golgi complex to the cell surface and between organelles. In this review we will discuss the role of soluble n-ethylmaleimide-sensitive factor attachment protein receptor proteins (SNAREs) in DCs both as facilitators of secretion and as useful tools to determine the pathways of secretion through their definite locations within the cells and inherent specificity in opposing binding partners on vesicles and target membranes. The role of SNAREs in DC function may present an opportunity to explore these proteins as novel targets in inflammatory disease.